2015
DOI: 10.1080/10615806.2015.1081178
|View full text |Cite
|
Sign up to set email alerts
|

The structure of DSM-5 posttraumatic stress disorder symptoms in war veterans

Abstract: The objective of the present research was to examine the underlying factor structure of posttraumatic stress disorder (PTSD) as conceptualized in the recently published fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5; APA, 2013). A self-report measure of PTSD symptoms was administered to 258 trauma-exposed Iraq/Afghanistan war veterans. Confirmatory factor analysis was used to compare several different models of PTSD. Confirmatory factor analysis revealed that the best-fitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Diagnostic rates are thus based on symptom criteria alone. Studies have reported acceptable psychometric properties for the PCL-5 (16). Reliability estimates among the current sample were satisfactory: I (a = .90), Av (a = .87), NACM (a = .84), and Ar (a = .78).…”
Section: Methodsmentioning
confidence: 65%
“…Diagnostic rates are thus based on symptom criteria alone. Studies have reported acceptable psychometric properties for the PCL-5 (16). Reliability estimates among the current sample were satisfactory: I (a = .90), Av (a = .87), NACM (a = .84), and Ar (a = .78).…”
Section: Methodsmentioning
confidence: 65%
“…Of the 22 studies fitting the most complex models, 19 tested the 7F hybrid model, and 16 found it best fitting. One (Konecky, Meyer, Kimbrel, & Morissette, 2016) attempted to test the 7F hybrid model and reported a Heywood case, resulting in fitting the next most complex model, the 6F anhedonia model. The 6F anhedonia model was the most complex model tested in two CFAs and fit best in those two and in a third in which it was judged superior to the 7F hybrid model.…”
Section: Resultsmentioning
confidence: 99%
“…The scale can be used to generate a self‐report DSM‐5 diagnosis using a cut‐point of 38. Studies have reported acceptable psychometric properties of the PCL‐5 scores in non‐clinical and trauma‐exposed samples . Wilkins et al provide a comprehensive review of the psychometric evaluation of earlier versions of the PCL.…”
Section: Methodsmentioning
confidence: 99%